Investigating hydrothermal pretreatment of food waste for two-stage fermentative hydrogen and methane co-production. (October 2017) - Ding, Lingkan; Cheng, Jun; Qiao, Dan; Yue, Liangchen; Li, Yu-You; Zhou, Junhu; Cen, Kefa
Highlights: Hydrothermal pretreatment (HTP) was used to facilitate food waste solubilization. Soluble carbohydrates initially rose and then fell when HTP temperature increased. Solubilization of proteins was dramatically promoted with increasing HTP temperature. Effect of HTP retention time on solubilization and fermentation was moderate. Two-stage H2 and CH4 co-production effected an energy conversion efficiency of 78.6%. Abstract: The growing amount of food waste (FW) in China poses great pressure on the environment. Complex solid organics limit the hydrolysis of FW, hence impairing anaerobic digestion. This study employed hydrothermal pretreatment (HTP) to facilitate the solubilization of FW. When HTP temperature increased from 100 to 200 °C, soluble carbohydrate content first increased to a peak at 140 °C and then decreased, whereas total carbohydrate content was negatively correlated with increasing temperature due to the enhanced degradation and Maillard reactions. Protein solubilization was dramatically promoted after HTP, whereas protein degradation was negligibly enhanced. The hydrogen and methane yields from hydrothermally pretreated FW under the optimum condition (140 °C, 20 min) through two-stage fermentation were 43.0 and 511.6 mL/g volatile solids, respectively, resulting in an energy conversion efficiency (ECE) of 78.6%. The ECE of pretreated FW was higher than that of untreated FW by 31.7%.